SCIENCES, LANGUAGES AND INTERDISCIPLINARITY IN THE CURRICULUM: A BIBLIOGRAPHICAL SEARCH (Interdisciplinary Studies Journal, 2024)
Interdisciplinarity in the curricular context represents an educational approach that transcends the traditional boundaries of academic disciplines, seeking to integrate knowledge, approaches and perspectives from different areas of knowledge. This approach aims to enrich students' understanding by promoting connections between different fields, allowing them to explore complex problems in a more holistic and contextualized way. By incorporating interdisciplinary elements into the curriculum, educational institutions aim to prepare students to face real-world challenges, where effective solutions often require collaboration between specialties. Furthermore, interdisciplinarity encourages skills such as critical thinking, problem solving and creativity, enabling students to become lifelong learners, capable of adapting to constantly evolving scenarios. In this sense, the present work involves a bibliographical review regarding the curriculum and possible interdisciplinary relationships between the areas of Natural Sciences and their Technologies and Languages ​​and their Technologies in High School.
Keywords: Science teaching; High school; Contextualization; Scientific language